Short pulse intense pulsed light versus pulsed dye laser for the treatment of facial redness. (17th February 2020) - Tirico, M. C. C. P.; Jensen, D.; Green, C.; Ross, E. V.
ABSTRACT: Treating diffuse facial redness with an intense pulsed light (IPL) source usually requires multiple sessions and may not achieve complete clearance. The 595 nm pulsed dye laser (PDL) enjoys a good reputation for reducing facial redness with non-purpuric settings. The objective of this study was to compare facial redness reduction using these two devices. After establishing the lowest light dose able to achieve transient purpura for the same pulse width of 1, 5 ms with each technology, right and left sides of the face were randomly assigned for each type of treatment. There were two treatment sessions 4 weeks apart and the final evaluation was performed 8 weeks after thesecond treatment. Four blinded experienced dermatologists analyzed pre and post-treatment photographs, which demonstrated an average of 60% improvement on the segment treated with the IPL as opposed to 45% on the other segment. Pain level was described as mild and the procedure was well tolerated for both types of treatment. In this study we showed that short-pulsed intense pulsed light and PDL are similar in decreasing facial redness when non-purpuric low fluence settings are used. The IPL was faster and did not have consumables.